Reading the forum page : an analysis of letters to the Straits Times forum page. - Wong, Teck Tian. (2008)
This thesis examines the types of letters published in the Straits Times Forum Page in the years 1996 and 2002, particularly the number of pro-government, critical and neutral letters published. The study explores the content of such letters and examines whether there are increases in the categories of letters between the two years. It also examines readers opinions of the use of the Forum Page. The study concludes that a greater variety of letters appeared in the Forum Page over the years, the newspaper published views of the public even if they are critical in content and there appears to be an equal balance between the critical and non critical letters published.